The Effect of Back Massage on the Intensity of Pain in Rheumatism Ladders - Chrismis Novalinda Ginting; Antonius Waruwu; Cahyanto Kurnia Mendrofa; Nita Tri Maria; Suci Syafira (Jurnal Penelitian Perawat Profesional, 2020)
Rheumatoid arthritis or RA for short, is a chronic, systematic disease of the musculoskeletal system. This disease is characterized by inflammation of the lining of the synovial joint. This chronic disease can cause pain and defomitas. Rheumatoid arthritis must be treated properly because the condition causes disruption of the activities of people with rheumatoid arthritis. The aim was to determine the effect of back massage on reducing pain intensity in elderly people with rheumatism. The research was conducted at the UPT Social Service for the Elderly of the Binjai Social Service 2020, when the study was conducted in September. The population in this study were 20 respondents who experienced rheumatism by using observation. It can be concluded that the results of the back message treatment with a Z value of 3,520 with a p-value of 0,000. From the p-value test value 0.000 <0.05. So that we can mean that Ho is rejected, and Ha is accepted and it can be concluded that there is an effect of back message on elderly people with rheumatism so that there is a difference between before (pre-test) and after (Post-test) back message is carried out.